STRUKTUR ILMU DALAM ISLAM DAN IMPLIKASINYA TERHADAP PENGEMBANGAN PENDIDIKAN ISLAM - Yoprisya, Yoprisya; Fikri, Kevin Ariful; Fadriati, Fadriati; Suryana, Ermis (Journal International Inspire Education Technology, 2025)
This study examines the structure of knowledge in Islam and its implications for the development of Islamic education within contemporary educational contexts. The background of this research is rooted in the ongoing epistemological crisis in Islamic education, particularly the persistence of the dichotomy between religious and secular sciences, which has weakened the integrative and value-oriented nature of Islamic education. The aim of this paper is to analyze the Islamic conception of the structure of knowledge and to explain how this structure provides a foundational framework for reconstructing the goals, curriculum, and pedagogical orientation of Islamic education. This study employs a qualitative approach through library research, utilizing classical and contemporary scholarly works on Islamic epistemology, philosophy of education, and Islamic educational thought. Data were analyzed using descriptive-analytical and comparative methods to identify core concepts, patterns, and relationships among key ideas. The findings reveal that the structure of knowledge in Islam is inherently integrative, grounded in the principle of tawhid, and unites revelation, reason, and empirical reality within a coherent epistemological system. This structure positions knowledge not only as a means of intellectual development but also as a moral and spiritual guide for human life. The study concludes that understanding and applying the Islamic structure of knowledge is essential for developing Islamic education that is holistic, value based, and responsive to modern challenges without losing its normative and spiritual foundations.